Nonlinear computer modeling of chemical and biochemical data - Rusling, James F; Kumosinski, Thomas F (Academic Press, 1996)
Assuming only background knowledge of algebra and elementary calculus, and access to a modern personal computer, Nonlinear Computer Modeling of Chemical and Biochemical Data presents the fundamental basis and procedures of data modeling by computer using nonlinear regression analysis.